COMPARISON OF WORK-LIFE BALANCE LEVELS OF SECURITY TEAM OFFICERS AT CLASS IIA CORRECTIONAL FACILITY IN SERANG AND CLASS IIB STATE DETENTION CENTER IN SERANG - Gifari, Muhammad Surya; Jarodi, Odi (Universitas Nusa Cendana, 2025)
Security guards play an important role in maintaining stability and security in correctional institutions and detention centers. Therefore, the balance between work and personal life (work-life balance) is a key factor that can affect their performance and well-being. This research focuses on comparing the level of work-life balance of security squad officers at the Class IIA Serang Correctional Institution and the Class IIB Serang State Detention Center. The formulation of the problem in this study is whether there is a significant difference in the level of work-life balance between officers in the two institutions. This study used a quantitative method with a cross-sectional survey approach, involving 72 respondents consisting of 36 officers in each institution. The data collection technique was conducted through a questionnaire with indicators measured based on the three main dimensions of work-life balance: time balance, involvement balance, and satisfaction balance. Data were analyzed using a normality test and t-test to see the difference between the two groups of respondents. The results showed a significant difference in the level of work-life balance between officers at Class IIA Serang Correctional Facility and Class IIB Serang Detention Center, with officers at the correctional facility showing higher scores. This improvement is due to factors such as the work environment, supporting facilities, and better management policies in correctional facilities. The conclusion of this study shows that work-life balance has a major influence on officers' well-being and performance, and there are significant differences between the two institutions. Keywords: Work-Life Balance; Security Squad Officers; Class IIA Serang Correctional Facility;, Class IIB Serang Detention Center